2023
DOI: 10.1101/2023.02.14.528555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inositol Pyrophosphate Dynamics Reveals Control of the Yeast Phosphate Starvation Program Through 1,5-IP8and the SPX Domain of Pho81

Abstract: Eukaryotic cells control cytosolic phosphate to balance its role as essential macronutrient with its negative bioenergetic impacts. Phosphate homeostasis depends on a conserved signaling pathway including inositol pyrophosphates (PP-IPs) and SPX receptor domains. Since cells synthesize various PP-IPs and SPX domains bind them promiscuously, it is unclear whether a specific PP-IP regulates SPX domains in vivo, or whether multiple PP-IPs act as a pool. In contrast to previous models, which postulated that phosph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Early studies postulated that P i starvation triggers an increase in 1-IP 7 , which should inactivate Pho85/Pho80 kinase by direct interaction with a central part of its regulatory subunit Pho81 ( 12 , 13 ). However, several subsequent studies failed to confirm the starvation-induced increase in IP 7 and instead showed a strong decline in the inositol phosphate pools after Pi starvation ( 5 , 9 , 14 ). These qualitatively different results on the inositol pyrophosphate pools and additional characterization of Pho81 led to a revised model of PHO pathway regulation in which 1,5-IP 8 controls Pho81 through its SPX domain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early studies postulated that P i starvation triggers an increase in 1-IP 7 , which should inactivate Pho85/Pho80 kinase by direct interaction with a central part of its regulatory subunit Pho81 ( 12 , 13 ). However, several subsequent studies failed to confirm the starvation-induced increase in IP 7 and instead showed a strong decline in the inositol phosphate pools after Pi starvation ( 5 , 9 , 14 ). These qualitatively different results on the inositol pyrophosphate pools and additional characterization of Pho81 led to a revised model of PHO pathway regulation in which 1,5-IP 8 controls Pho81 through its SPX domain.…”
Section: Introductionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , INPHORS triggers the PHO pathway, the transcriptional phosphate starvation response that controls expression of genes for P i scavenging, uptake, and recycling ( 9 ). The PHO pathway in yeast is controlled through the transcription factor Pho4, which accumulates in the nucleus after P i starvation and interacts with another transcription factor, Pho2, to activate many P i -dependent genes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 O-water can be obtained in 99.5% pure form, enabling labeling to very high specific isotope content. This facilitates detection of inositol phosphates by mass spectrometry, some of which exist is sub-micromolar concentrations in cells (Chabert et al , 2023; Harmel et al , 2019; Barker et al , 2004; Albert et al , 1997). 18 O-water labeling can be performed in any medium and under any growth condition.…”
Section: Discussionmentioning
confidence: 99%